Partial structural characterization of pectin cell wall from Argania spinosa leaves - Kadda Hachem; Yasmina Benabdesslem; Samia Ghomari; Okkacha Hasnaoui; Meriem Kaid-Harche (Heliyon, 2016)
The pectin polysaccharides from leaves of Argania spinosa (L.) Skeels, collected from Stidia area in the west coast of northern Algeria, were investigated by using sequential extractions and the resulting fractions were analysed for monosaccharide composition and chemical structure. Water-soluble pectic (ALS-WSP) and chelating-soluble pectic (ALS-CSP) fractions were obtained, de-esterified and fractionated by anion-exchange chromatography and characterized by sugar analysis combined with methylation analysis and 1H and 13C NMR spectroscopy. The data reveal the presence of altering homogalacturonan (HG) and rhamnogalacturonan I (RG-I) in both pectin fraction. The rhamnogalacturonan I (RG-I) are consisted of a disaccharide repeating unit [→ α-D-GalpA-1,2-α-L-Rhap-1,4 →] backbone, with side chains contained highly branched α-(1 → 5)-linked arabinan and short linear β-(1 → 4)-linked galactan, attached to O-4 of the rhamnosyl residues.